Pressure manipulation of exciton dynamics in few-layered MoS2. Issue 13 (January 2020) - Li, Q; Sui, L; Jiang, Y; Chen, A; Jin, W; Liu, H; Yuan, K; Jin, M
Synopsis: Transition metal dichalcogenides have recently attracted great interest as an important class of two-dimensional semiconductors because of their distinctive electronic, optical and catalytic properties. Here we demonstrate the first experimental study on ultrafast excited state dynamics of few-layered molybdenum disulfide under high pressure by means of broadband transient absorption spectroscopy combined with diamond anvil cell devices.